Asymmetric one storey elastic systems with non linear viscous and viscoelastic dampers Earthquake response. - Lin, Wen-Hsiung (Earthquake engineering & structural dynamics.)
Investigated are earthquake responses of one way symmetric plan, one storey systems with non linear fluid viscous dampers (FVDs) attached in series to a linear brace (i.e. Chevron or inverted V-shape braces). Thus, the non linear damper is viscous when the brace is considered rigid or viscoleastic (VE) when the brace is flexible. The energy dissipation capacity of a non linear FVD is characterized by an amplitude dependent damping ratio for an energy equivalent linear FVD, which is determined assuming the damper undergoes harmonic motion. Although this formulation is shown to be advantageous for single degree of freedom (SDF) systems, it is difficult to extend its application to multi degree of freedom (MDF) systems for two reasons : (1) the assumption that dampers undergo harmonic motion in parameterizing the non linear damper is not valid for its earthquake induced motion of an MDF system; and (2) ensuring simultaneous convergence of all unknown amplitudes of dampers is difficult in an iterative solution of the non linear system. To date, these limitations have precluded the parametric study of the dynamics of MDF systems with non linear viscous or VE dampers. However, they are overcome in this investigation using concepts of modal analysis because the system is weakly non linear due to supplemental damping. It is found that structural response is only weakly affected by damper non linearity and is increased by a small amount due to bracing flexibility. Thus, the effectiveness of supplemental damping in reducing structural responses and its dependence on the planwise distribution of non linear VE dampers were found to be similar to that of linear FVDs documented elsewhere. As expected, non linear viscous and VE dampers achieve essentially the same reduction in response but with much smaller damper force compared to linear dampers. Finally, the findings in this investigation indicate that the earthquake response of the asymmetric systems with non linear viscous or VE dampers can be estimated with sufficient accuracy for design applications by analysing the same asymmetric systems with all non linear dampers replaced by energy equivalent linear viscous dampers.